METHODOLOGY OF FUTURE DENTISTS’ FOREIGN LANGUAGE COMPETENCE FORMATION ON THE BASE OF CAMBRIDGE METHODS OF ENGLISH LANGUAGE TEACHING - Kulbashna, Yaroslava; Zakharova, Valeriia (The Modern Higher Education Review, 2018)
The article deals with the improvement of future dentists’ foreign language competence formation based on the Cambridge methods of English language teaching. Future dentists have a strong need to receive professional knowledge from foreign sources and communicate to their colleagues. Moreover the foreign language competence is an important part of professional competence. Thus foreign language competence formation of future dental specialists contains certain diversity; it is not typical for other specialties. As a result it requires thorough analysis of Cambridge methods of English language teaching in order to adapt and improve them for future dentists. On the base of own pedagogical experience this advanced methodology was designed as student-centered one and includes new improved tasks for better language competence formation. Original Cambridge methodology was also improved by implementing the new “verification” stage of the lesson. This methodology was applied at the Bologolets Nalional Medical University and has brought positive results. It will become the base of increasing level of competitiveness not only in our country and abroad as well.